ON ADMISSION TO THE CLERGY: VOCATION AND FAMILY STRATEGIES IN EIGHTEENTH CENTURY SPAIN - Irigoyen López, Antonio (Revista de Historia Social y de las Mentalidades, 2017)
This paper aims to reflect on the reasons why  people decided to become clerics. For this we  will resort to the analysis of various works  of ecclesiastical treatises written in Spain  during the eighteenth century. It is verified  that joining the Church was not a free and  personally decision taken by those involved,  but other reasons were considered, in  particular family strategies: someone entered  the Church to favor his family. Faced with  this situation, ecclesiastical texts advocated  that people should only enter the Church with  true vocation, otherwise, would never be good  ecclesiastical ministers. This reality was very  common in Eighteenth Century Spain, which  should be corrected through written plays for  the priests became aware of the importance of  their mission
Keywords: Church; Clergy; Vocation; Family; Strategies; Ecclesiastical Treatises